INTERPRETATION OF NERVE CONDUCTION STUDY IN POLYNEUROPATHY WITH MULTIBACILLARY LEPROSY TYPE 2 REACTION - Sari, Diane Tantia; Widasmara, Dhelya; Kurniawan, Shahdevi Nandar (Malang Neurology Journal, 2018)
Leprosy reaction contributes to disability due to peripheral nerve damage. Nerve conduction study (NCS) provides a profound physiological description of peripheral nerves. This study aims to report a case of polyneuropathy in leprosy with type 2 reactions (T2R) which is evaluated using NCS. A 33-year-old woman complain of painful bumps in her arms and legs, fever, swollen feet since 2 days ago, and history of leprosy. Dermatologic examination on the right superior palpebra, right and left arms and legs revealed multiple tenderness erythematous nodules; right claw hand; and both legs oedema. Slit skin smear revealed positive result. Histopathologic examination supported T2R description. The NCS examination concluded severe axonal demyelinating motoric sensoric polyneurophaty, with left worse. She was treated with MDT-MB, bed rest, orally methylprednisolone, vitamin B, paracetamol, ferrous sulfas, and topical olive oil. Clinical improvement was achieved after 2 weeks. The NCS is used to assess the nerve impuls conduction along the peripheral nerves. In this case, it was found that NCS could showed early neuropathy in nerves that were clinically undetectable. It can be concluded that the NCS examination is an important diagnostic modalities for early detection of neuropathy and confirmed the diagnosis of clinical neuropathy in leprosy.